Therapeutic Application of Phage Capsule Depolymerases against K1, K5, and K30 Capsulated E. coli in Mice - Lin, Han; Paff, Matthew L.; Molineux, Ian J.; Bull, James J. (Frontiers in Microbiology, 2017)
Capsule depolymerase enzymes offer a promising class of new antibiotics. In vivo studies are encouraging but it is unclear how well this type of phage product will generalize in therapeutics, or whether different depolymerases against the same capsule function similarly. Here, in vivo efficacy was tested using cloned bacteriophage depolymerases against E. coli strains with three different capsule types: K1, K5, and K30. When treating infections with the cognate capsule type in a mouse thigh model, the previously studied K1E depolymerase rescued poorly, whereas K1F, K1H, K5 and K30 depolymerases rescued well. K30 gp41 was identified as the catalytically active protein. In contrast to the in vivo studies, K1E enzyme actively degraded K1 capsule polysaccharide in vitro and sensitized K1 bacteria to serum killing. The only in vitro correlate of poor K1E performance in vivo was that the purified enzyme did not form the expected trimer. K1E appeared as an 18-mer which might limit its in vivo distribution. Overall, depolymerases were easily identified, cloned from phage genomes, and as purified proteins they proved generally effective.